The Boundary Waters Wilderness ecosystem - Heinselman, Miron L. (Minneapolis : University of Minnesota Press, 1996)
A guide to the history, landscape, climate, forests, wildlife, and the location of natural features and historic sites in the Boundary Waters region of northern Minnesota and southern Ontario.
Includes bibliographical references (p. [315]-324) and index.
Choice.
Adult
Keywords: Ecology -- Minnesota -- Boundary Waters Canoe Area; Natural history -- Minnesota -- Boundary Waters Canoe Area; Ecology; Natural history -- Boundary Waters Canoe Area (Minn.); Boundary Waters Canoe Area (Minn.); Boundary Waters Canoe Area (Minn.)